GC–MS CHARACTERIZATION OF FATTY ACID ALKYL ESTERS IN BIODIESEL PRODUCED FROM WASTE COOKING OIL - Gading Bagus Mahardika; Agung Prabowo; Syarifuddin Oko; Muh Irwan; Alvyano (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2026)
This study aims to identify and characterize the major compounds in biodiesel produced through the transesterification of vegetable oils using Gas Chromatography–Mass Spectrometry (GC–MS). The analysis was conducted to evaluate the composition of fatty acid esters—specifically Fatty Acid Methyl Esters (FAME) and Fatty Acid Ethyl Esters (FAEE)—which play a crucial role in determining biodiesel quality. Three biodiesel samples were analyzed, revealing dominant peaks at retention times between 15 and 17 minutes, identified as methyl palmitate (C₁₇H₃₄O₂), methyl oleate (C₁₉H₃₆O₂), and methyl stearate (C₁₉H₃₈O₂). The total content of these major esters ranged from 85% to 92%, indicating an efficient conversion of triglycerides into esters. The resulting chemical profile exhibited a balanced proportion of saturated and unsaturated compounds, providing high oxidative stability and favorable cold flow properties. These findings demonstrate that the produced biodiesel meets the requirements of international standards ASTM D6751 and EN 14214, confirming its potential as an environmentally friendly alternative fuel.